New-Fangled Marketing Practices in Rural India: Understanding the dynamics and challenges of rural marketing in India (Journal of Advances and Scholarly Researches in Allied Education, 2011)
Rural marketing facilitate flow of goods and service from rural producers to urban consumers at possible time with reasonable prices, and agriculture inputs/consumer goods from urban to rural. Marketing as a function has started much earlier when civilization started but not recognized as marketing. All economy goods are marketed in terms of goods and services (Barter system). Now money is being practiced as a good exchanging medium. The market may be a street, small town or metropolitan city. Developments in infrastructure, transport, and communication facilities have increased the scope of the rural market. Indian rural marketing has always been complex to forecast and consist of special uniqueness. As two-thirds of the Indian population live in rural areas, the market is vast than expected and so many companies are doing very good business in the rural market of India. This paper discusses the present scenario of rural marketing in India and its importance, available opportunities, and also highlights the influencing factors and certain problems related to rural marketing. Further it highlights the improvements that make the rural marketing system most effective.